Psychometric properties and normative data of the ECCO_Senior test: an instrument to assess grammatical comprehension in older adults - López-Higes, Ramón; Rubio-Valdehita, Susana; Sánchez-Beato, Andrea; Galindo, Marta; Mecha, Patricia Regina; García Cid, Sophie; Llorente, Cristina (Revista de Investigación en Logopedia, 2020)
The ECCO_Senior test was designed to assess sentence comprehension in older adults. It is a short test and easy to apply, which has been used in different previous studies. The study involved 670 people, 50 to 85 years of age, who met inclusion criteria related to general cognitive status, mood and minimum percentage of performance in the test. In addition to the screening tests (MEC and GDS-15) and a socio-demographic questionnaire, the ECCO_Senior test was applied to all participants with which different indices (general and specific) can be obtained. In addition to checking if there are differences between the groups according to age and educational level, we evaluated the psychometric properties of the test, evidences of validity included, thus we tested the goodness of fit of three structural models that serve to identify the indices that explain a greater percentage of the variance of the construct (comprehension of sentences). Interpretive norms of the test are offered by age and level of studies in the Appendices. The results indicate that the test allows to evaluate sentence comprehension with adequate reliability and it is sensitive to the difficulties that an adult may experience when performing this task. The three models show a good fit and allow us to conclude that the sentences not adjusted to the canonical syntactic order and lexical foils (if the type of item is considered) would be the best indexes in terms of the percentage of construct’s variance they explain.
Keywords: assessment; grammatical comprehension; older adults; interpretative norms